Influence of homeomorphism of the surface of a wood particle on the characteristics of its ignition. (February 2023) - Kuznetsov, G.V.; Syrodoy, S.V.; Borisov, B.V.; Kostoreva, Zh.A.; Gutareva, N. Yu; Kostoreva, A.A.
Abstract: The article presents the results of the experimental studies carried out to analyze the connections between the configuration of the particles and the delay time of their ignition. The results of the experimental studies of the ignition processes of woody biomass particles of various shapes and sizes, but identical volumes, as applied to the heating conditions in the combustion chambers of the typical boiler units, are obtained. Three shapes of wood particles were studied: a rectangular parallelepiped, a cube, and a plate. Quite non-obvious (based on traditional concepts) dependences of the ignition delay times on the characteristic sizes of wood particles have also been established: under conditions of relatively low ambient temperatures (Tg  = 873K), the characteristic size and shape have a significant effect on the characteristics and conditions of ignition. In the case of ignition of plates, the dependence tign (δ) is linear; in the case of ignition of cubic particles, the dependence tign (δ) is nonmonotonic with a local minimum; in the case of ignition of biomass particles in the form of parallelepipeds, the function tign (δ) has a nonmonotonic character with a local maximum of the value of tign .